New insights into the transcription factor regulatory networks driving peel coloration under hormone induction analyzed by transcriptomics and metabolomics in tangor ‘Murcot’ - Chen, Yang; Yang, Lei; Li, Shuang; Wang, Min; Yu, Jianjun; Bai, Wenqin; Hong, Lin (Frontiers in Plant Science, 2025)
IntroductionFruit color is a crucial quality factor strongly influencing consumer preference for citrus. The coloration of citrus fruit is primarily determined by carotenoids, which produce a range of hues. Gibberellic acid (GA) and ethylene are critical in fruit coloration during the ripening process. Nevertheless, the underlying mechanisms remain poorly understood.MethodsThe present study utilized transcriptomic and metabolomic analyses to investigate the molecular regulatory mechanisms affecting peel pigment metabolism in tangors (Citrus reticulata Blanco×Citrus sinensis L. Osbeck) following GA and ethephon (ETH) treatments.Results and discussionCollectively, our findings indicated that GA inhibits chlorophyll degradation and the accumulation of numerous carotenoids, including five violaxanthin esters (violaxanthin palmitate, violaxanthin myristate–caprate, violaxanthin myristate–laurate, violaxanthin dilaurate, violaxanthin myristate) and two β-cryptoxanthin derivatives (β–cryptoxanthin laurate, β–cryptoxanthin myristate), while ETH promotes these processes. Furthermore, GA inhibited the downregulation of lutein, the predominant carotenoid in immature fruits. Notably, integrated transcriptomic and metabolomic analyses identified 33 transcription factors associated with pigment metabolism. Of these, two novel transcription factors, the ethylene-responsive transcription factor ABR1 and the HD-Zip transcription factor ATHB7, were uncovered through both transcriptomic analysis and weighted gene co-expression network analysis. These two transcription factors positively regulated the colouration process, as validated by transient overexpression assays in tobacco. Taken together, our findings elucidated the global carotenoid changes and transcriptional alterations in regulating citrus peel color under hormone induction, with significant implications for improving citrus production.